Pengaruh Sustainable Fashion, Slow Fashion dan Fast Fashion terhadap Environmental Sustainability - Hermawan, Budi Dharma; Astono, Anjar Dwi (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
Technological advancements have transformed fashion into a form of self-expression and culture. The fashion industry in Indonesia has had a positive economic impact but poses challenges to environmental sustainability. Gen-Z tends to favor Fast Fashion, which pollutes the environment with textile waste. Conversely, Slow Fashion and Sustainable Fashion emphasize quality, production ethics, and environmentally friendly materials. This study explores the influence of these three fashion concepts on environmental sustainability. Slow Fashion and Sustainable Fashion can reduce the negative impact of the fashion industry through sustainable practices and recycled materials. This research focuses on the importance of shifting consumption towards more responsible fashion to preserve the environment. The research method used is quantitative, distributing questionnaires to a population of 142 respondents using non-probability sampling techniques, and processed using SPSS 29.